Effectiveness of a nanofiltration membrane-based recirculation system on growth and survival of asian redtail catfish (Hemibagrus nemurus) under various retentate treatments - Mulyadi; Ayu Pamukas Niken; Adelina; Putra Iskandar; Hidayah Sulaiman Nurul; Parmono Tri (BIO Web of Conferences)
Recirculated Aquaculture Systems (RAS) is an efficient, stable, and easily controllable method of aquaculture. By utilizing nanofiltration, these systems improve water quality in the pond, which in turn promotes better fish growth. The purpose of this study is to assess the optimal management of retentate flow in rearing systems utilizing nanofiltration membrane technology, aimed at improving the growth performance and survival rate of Asian redtail catfish. The research follows a Completely Randomized Design (CRD) with one factor, five treatment levels and three repetitions. The treatment levels are as follows: P1 = discarding 40% of the retentate, P2 = discarding 50% of the retentate, P3 = discarding 60% of the retentate, P4 = discarding 70% of the retentate, and P5 = discarding 80% of the retentate. The best results were obtained in P2, with an average absolute weight growth of 6.45±0.42 g, absolute length growth of 4.79±0.19 cm, specific growth rate of 4.82±0.19%, feed efficiency of 77.35±1.08%, feed conversion ratio of 1.29±0.01, survival rate of 90.62±3.12%, and water quality within the rearing media suitable for Asian redtail catfish growth and survival. The glucose levels observed during the study ranged from 47 to 61 mg dL-1.